Parietal and occipital hair loss patterns in initial stages of androgenic alopecia in men - Irina N. Kondrakhina; Dmitry A. Verbenko; Alexander M. Zatevalov; Dmitry G. Deryabin (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
Background. The initial stages of androgenetic alopecia in men are characterized by a variety of clinical manifestation in the parietal or occipital scalp regions. However, the differences in the pathogenesis of hair loss patterns are not well understood, selective treatment has not been developed. Aims. Trichological characteristics of patients with initial stages of androgenetic alopecia with identification of genetic and non-genetic factors that determine the hair loss in the different scalp regions, and their response to conservative therapy. Materials and methods: Trichograms were photodocumented using an AramoSG microcamera (Republic of Korea). The genetic factor was analyzed by mini-sequencing of single nucleotide polymorphisms rs929626, rs5919324, rs1998076, rs12565727, rs756853. The non-genetic factors study included hormonal status (total and free testosterone, dihydrotestosterone, 17OH-progesterone, dehydroepiandrostenone, SHBG) and blood content of trace elements (Mg, Ca, Zn, Cu, Se, Fe) and vitamins (B12, D, E, folic acid). Conservative treatment was topical application of a minoxidil 5% (twice-a-day, 4 months) and a micronutrient deficiencies personalized correction. Results. The study included 47 man with initial stages of androgenetic alopecia. Their trichological examination showed two patterns, consisting a predominant decrease in the hair density and diameter in the parietal and occipital scalp regions, which were subgroups formation criteria. An intergroup comparison revealed similar genetic risk, while hormonal parameters (increased dihydrotestosterone levels, a decrease in free testosterone) characterized the subgroup with parietal hair loss pattern. Also, a multiple deficiency of Zn, Cu, Se and vitamins B12, D, folic acid was detected in all patients. Subsequent conservative treatment had a positive effect in patients with parietal hair loss pattern, while in patients with occipital pattern no significant response was observed. Conclusions. The study develops ideas about differences between androgen-dependent parietal and androgen-independent occipital hair loss patterns in the initial stages of androgenetic alopecia, which requires different approaches to their conservative therapy.